Sub-lethal exposure to cold atmospheric plasma in vitro induces changes in bacterial antibiotic resistance profiles. A pilot study. - Martínez-Barrera, Melina E.; Bustos Martinez, Jaime; Sánchez-Pérez, Leonor; Hamdan-Partida, Aída; Acosta-Gio, A Enrique (International Journal of Infection Control, 2019)
To evaluate the effect of sub-lethal exposure to cold atmospheric plasma (CAP) on their antibiotic resistance, Methicillin Resistant Staphylococcus aureus, S. epidermidis, Pseudomonas aeruginosa, Escherichia coli, Streptococcus mutans, and Candida albicans were exposed in vitro to a commercially available CAP. This antimicrobial CAP inhibited growth but changed survivors’ antibiotic resistance.